SECONDARY SCHOOLS STUDENT’S PERCEPTIONS OF USING THE DUOLINGO APP TO LEARN ENGLISH IN AN EFL CONTEXT - Sugianto, Larasati Sekar Arum; Prasetyarini, Aryati (Program Studi Pendidikan Bahasa Inggris Fakultas ilmu Budaya, 2025)
This study aims to find out how high school students perceive the Duolingo app as a medium for learning English in the classroom. It also aims to analyze the impact of the app on students' English proficiency and evaluate how students respond to learning using the app. The methodology used in this high school research is semi-structured interview and school observation using qualitative research approach to collect data. The results of the data obtained by the researcher, showed that using the Duolingo application as an English learning media succeeded in increasing the percentage of students' interest in learning English as a foreign language, so that students can easily learn English and explore various skills by practicing questions that have been provided in the application. Applying the media in the learning process also supports students to learn English independently.